Tau Oligomers Associate with Inflammation in the Brain and Retina of Tauopathy Mice and in Neurodegenerative Diseases - Nilson, Ashley N.; English, Kelsey C.; Gerson, Julia E.; Barton Whittle, T.; Nicolas Crain, C.; Xue, Judy; Sengupta, Urmi; Castillo-Carranza, Diana L.; Zhang, Wenbo; Gupta, Praveena; Kayed, Rakez (Journal of Alzheimer's disease, 2017)
It is well-established that inflammation plays an important role in Alzheimer’s disease (AD) and frontotemporal lobar dementia (FTLD). Inflammation and synapse loss occur in disease prior to the formation of larger aggregates, but the contribution of tau to inflammation has not yet been thoroughly investigated. Tau pathologically aggregates to form large fibrillar structures known as tangles. However, evidence suggests that smaller soluble aggregates, called oligomers, are the most toxic species and form prior to tangles. Furthermore, tau oligomers can spread to neighboring cells and between anatomically connected brain regions. In addition, recent evidence suggests that inspecting the retina may be a window to brain pathology. We hypothesized that there is a relationship between tau oligomers and inflammation, which are hallmarks of early disease. We conducted immunofluorescence and biochemical analyses on tauopathy mice, FTLD, and AD subjects. We showed that oligomers co-localize with astrocytes, microglia, and HMGB1, a pro-inflammatory cytokine. Additionally, we show that tau oligomers are present in the retina and are associated with inflammatory cells suggesting that the retina may be a valid non-invasive biomarker for brain pathology. These results suggest that there may be a toxic relationship between tau oligomers and inflammation. Therefore, the ability of tau oligomers to spread may initiate a feed-forward cycle in which tau oligomers induce inflammation, leading to neuronal damage, and thus more inflammation. Further mechanistic studies are warranted in order to understand this relationship, which may have critical implications for improving the treatment of tauopathies.